The Role of Company Image and Employee Perceptions in Attracting and Retaining Foreign Working-Level Talent in the Finnish Staffing Industry - Heikkinen, Niklas (My University, 2023)
The Finnish staffing industry has been facing a shortage of skilled labor in recent years, with increasing competition for talent from other countries. In order to attract and retain foreign working-level employees, staffing companies in Finland must understand the factors that influ- ence the employee's decision to move to and stay in the country. This study aims to examine the role of company image and employee perceptions in attracting and retaining foreign work- ing-level talent in the Finnish staffing industry. The study will focus on the factors that affect the employee's decision to move to and stay in Finland, including company image, job satisfaction, career opportunities, and quality of life. The study will also examine the strategies that staffing companies in Finland are currently using to attract and retain foreign working-level employees and will provide recommendations for improving these strategies. The research design is qualitative in nature, and semi-structured interviews are conducted with foreign working-level talent. Working-level talent, also known as blue-collar employees, refers to individuals who perform manual or physical labor in industries such as manufacturing, con- struction, transportation, and maintenance. Interviewing working-level talent provides primary data, in-depth understanding, contextualization, and contributes to literature on employer at- tractiveness and retention in the Finnish staffing industry. The data collected from the inter- views will be analyzed using thematic analysis to identify key themes and patterns related to company image and employee perceptions that may impact the attraction and retention of for- eign working-level talent. This master's thesis reveals that a favorable company image and positive employee perceptions about a company significantly contribute to the attraction and retention of foreign working-level talent in the Finnish staffing industry. The study shows that employee satisfaction and trust, along with social support and professional growth opportunities, have significant importance for the working-level talent. These findings underscore the significance of creating a welcoming and inclusive work environment to effectively engage and retain foreign employees. The results sug- gest that staffing companies in Finland can improve their strategies by focusing on enhancing their employer brand, fostering a supportive and inclusive culture, and providing avenues for the professional development of their foreign workforce.

Suomen henkilöstöpalvelualalla on viime vuosina ollut haasteita palkata pätevää työvoimaa kil- pailun kiristyessä muiden maiden työntekijöiden kanssa. Jotta suomalaiset henkilöstöpalveluyri- tykset voisivat houkutella ja pitää kiinni ulkomaisista työntekijöistä, heidän täytyy ymmärtää ne tekijät, jotka vaikuttavat työntekijän päätökseen muuttaa Suomeen ja pysyä siellä. Tämä tutki- mus keskittyy tutkimaan yrityksen maineen ja työntekijän näkemysten roolia ulkomaisen työ- voiman houkuttelussa ja säilyttämisessä Suomen henkilöstöpalvelualalla. Tutkimuksessa tarkas- tellaan erilaisia tekijöitä, jotka vaikuttavat työhön muuttoon ja Suomessa pysymiseen, kuten yri- tyksen maine, tyytyväisyys työhön, uramahdollisuudet ja elämänlaatu. Lisäksi tutkimuksessa tar- kastellaan niitä strategioita, joita suomalaiset henkilöstöpalveluyritykset käyttävät tällä hetkellä ulkomaisen työnvoiman houkuttelemiseksi ja säilyttämiseksi sekä annetaan suosituksia näiden strategioiden parantamiseksi. Tutkimus on toteutettu laadullisesti, ja ulkomaisille työntekijöille on tehty puolistrukturoituja haastatteluja. Työntekijätasolla tarkoitetaan yksilöitä, jotka työskentelevät manuaalisissa tai fyysisissä töissä teollisuuden aloilla, kuten valmistus, rakentaminen, kuljetus ja kunnossapito. Työntekijätason haastattelut tarjoavat ensisijaista tietoa, syvällistä ymmärrystä ja kontekstia liit- tyen yrityksen houkuttelevuuteen ja säilyttämiseen Suomen henkilöstöpalvelualalla. Haastatte- luista kerättyjä tietoja analysoitiin teema-analyysin avulla tunnistaaksemme keskeisiä teemoja ja kaavoja, jotka liittyvät yrityksen maineeseen sekä työntekijän näkemyksiin ja voivat vaikuttaa ulkomaisen työnvoiman houkutteluun ja säilyttämiseen. Tämän opinnäytetyön tutkimus osoittaa, että positiivinen yrityskuva sekä myönteiset työnteki- jän näkemykset yrityksestä ovat merkittävässä roolissa ulkomaisen työnvoiman houkuttelussa ja säilyttämisessä Suomen henkilöstöpalvelualalla. Tutkimukset viittaavat siihen, että työnteki- jän tyytyväisyys ja luottamus, sosiaalinen tuki ja mahdollisuudet ammatilliseen kasvuun ovat merkittäviä tekijöitä organisaatiotasolla. Tulokset korostavat suomalaisten henkilöstöpalveluyri- tysten mahdollisuuksia parantaa strategioitaan keskittymällä yrityksen maineen vahvistamiseen työnantajana, edistämällä avointa ja osallistavaa työympäristöä sekä tarjoamalla ulkomaisille työntekijöille mahdollisuuksia ammatilliseen kehittymiseen.
Keywords: fi=Kansainvälinen liiketoiminta|en=International Business|; Master's Degree Programme in International Business